PRIA DI MATA PRIA: Resepsi Khalayak Konsumen Pria di Platform Kaskus terkait Kampanye Garnier Men - Surbakti, Abbram Mika Teguh (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2016)
Kaskus is an Indonesia forum site with a really huge user base, in Indonesia, it’s popularity is on the same level as some global sites such as Google, Youtube, Twitter, and many more. Seeing from this fact alone, it’s easy to say Kaskus as potential promotional media in Indonesia. The problem is, there’s some misunderstanding about Kaskus, especially the users, which make some brands ignoring Kaskus as of their potential promotional media for their campaign. Garnier, on the other hand, is one of the brands brave enough to use Kaskus as one of their promotional media for the Garnier Urban Hero which talks about masculinity. This article explores this campaign from the perspective of consumers, especially men as the dominant users of Kaskus. Using reception analysis with Hall’s Encoding/Decoding as it’s the basic idea, the study has identified how the reception process of Kaskus users from this campaign worked, how they interpreting it, how they decoding it, and then how users were understanding or interpreting Kaskus itself. Men saw other men on media as the mirror as well as competitor for their desire and pleasure. The brand is a vehicle for connecting men's desire and their repressing pleasures in facing the competition. To cite this article (7th APA style): Surbakti, A. M. T. (2016). Pria di Mata Pria: Resepsi Khalayak Konsumen Pria di Platform Kaskus terkait Kampanye Garnier Men [Men Reception towards the Campaign of Garnier Men in Kaskus]. Journal Communication Spectrum, 6(1), 74-88